A Half-Day Genome Sequencing Protocol for Middle East Respiratory Syndrome Coronavirus - Kim, Kwan Woo; Choi, Sungmi; Shin, Su-Kyoung; Lee, Imchang; Ku, Keun Bon; Kim, Seong Jun; Kim, Seil; Yi, Hana (Frontiers in Microbiology, 2021)
Recent coronavirus (CoV) outbreaks, including the Middle East respiratory syndrome (MERS), have presented a threat to public health worldwide. A primary concern in these outbreaks is the extent of mutations in the CoV, and the content of viral variation can be determined only by whole genome sequencing (WGS). We aimed to develop a time efficient WGS protocol, using universal primers spanning the entire MERS-CoV genome. MERS and synthetic Neoromicia capensis bat CoV genomes were successfully amplified using our developed PCR primer set and sequenced with MinION. All experimental and analytical processes took 6 hours to complete and were also applied to synthetic animal serum samples, wherein the MERS-CoV genome sequence was completely recovered. Results showed that the complete genome of MERS-CoV and related variants could be directly obtained from clinical samples within half a day. Consequently, this method will contribute to rapid MERS diagnosis, particularly in future CoV epidemics.